Integral of 3x-3/√1-x²dx dx
The solution
Detail solution
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−x2)dx=−∫x2dx
-
The integral of xn is n+1xn+1 when n=−1:
∫x2dx=3x3
So, the result is: −3x3
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫3xdx=3∫xdx
-
The integral of xn is n+1xn+1 when n=−1:
∫xdx=2x2
So, the result is: 23x2
-
The integral of a constant is the constant times the variable of integration:
∫(−13)dx=−3x
The result is: 23x2−3x
The result is: −3x3+23x2−3x
-
Now simplify:
6x(−2x2+9x−18)
-
Add the constant of integration:
6x(−2x2+9x−18)+constant
The answer is:
6x(−2x2+9x−18)+constant
The answer (Indefinite)
[src]
/
| 3 2
| / 3 2\ x 3*x
| |3*x - ----- - x | dx = C - 3*x - -- + ----
| | ___ | 3 2
| \ \/ 1 /
|
/
∫(−x2+(3x−13))dx=C−3x3+23x2−3x
The graph
Use the examples entering the upper and lower limits of integration.